Beyond aerodynamics: The critical roles of the circulatory and tracheal systems in maintaining insect wing functionality - Pass, Günther (Ventricular Restraint Improves Outcomes in HF Patients with CRT, 2018)
Insect wings consist almost entirely of lifeless cuticle; yet their veins host a complex multimodal sensory apparatus and other tissues that require a continuous supply of water, nutrients and oxygen. This review provides a survey of the various living components in insect wings, as well as the specific contribution of the circulatory and tracheal systems to provide all essential substances. In most insects, hemolymph circulates through the veinal network in a loop flow caused by the contraction of accessory pulsatile organs in the thorax. In other insects, hemolymph oscillates into and out of the wings due to the complex interaction of several factors, such as heartbeat reversal, intermittent pumping of the accessory pulsatile organs in the thorax, and the elasticity of the wall of a special type of tracheae. A practically unexplored subject is the need for continuous hydration of the wing cuticle to retain its flexibility and toughness, including the associated problem of water loss due to evaporation. Also, widely neglected is the influence of the hemolymph mass and the circulating flow in the veins on the aerodynamic properties of insect wings during flight. Ventilation of the extraordinarily long wing tracheae is probably accomplished by intricate interactions with the circulatory system, and by the exchange of oxygen via cutaneous respiration.